Construction of a mathematical model of an induction motor for a transport power plant incorporating magnetic saturation processes - Kulagin, Dmytro; Maslov, Igor (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers the electromagnetic and electromechanical processes in a traction induction motor. The task addressed relates to the absence of a universal mathematical model of a high-power induction motor that accounts for magnetic circuit saturation, cross-saturation, and core losses. Such a model is required for an adequate description of transient processes under the operating conditions of marine power plants. The essence of the results reported here is the construction of a system of equations describing the electromagnetic and electromechanical processes in a traction induction motor, taking into account magnetic circuit saturation. The proposed model includes four differential and two algebraic equations, providing complete controllability over the machine dynamics on both linear and nonlinear segments of the magnetization characteristic. By applying the dynamic inductance method, the model accounts for the interdependence between flux linkages and currents in different coordinate axes, as well as for the nonlinear variations of inductance parameters under magnetic saturation. These specific features have made it possible to accurately reproduce the real physical processes in the motor, as confirmed by bench verification based on the Caterpillar 3516 marine power plant. The results are attributed to the use of a generalized spatial model and dynamic inductances that reflect the variability of the motor’s magnetic state under different load conditions. The built model could be used in the synthesis of automatic control systems, analysis of transient processes, diagnostics of electric drives, as well as optimization of power plants. It could be practically implemented under conditions of stable thermal regime of the motor and availability of reliable experimental data for identification of saturation parameters